Flame-retardant microcapsule, preparation method thereof and battery

By using high ionic conductivity inorganic substances to modify the flame-retardant microcapsules of polymer shells in lithium batteries, the safety problem of lithium batteries under harsh conditions is solved, and safety is improved without affecting the electrochemical performance.

CN119701810APending Publication Date: 2025-03-28SICHUAN ANGAO SPECIAL ELECTRIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411873214.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing lithium batteries are prone to toxicity, flammability, potential leakage and even explosion accidents under harsh conditions, and improved measures to improve safety usually affect electrochemical performance.

Method used

Flame retardant microcapsules with core-shell structure are used. The shell is composed of inorganic modified polymers. The surface lithium ion conductivity is high, and it can remain intact when the battery is working normally. When the flame retardant is released in extreme working conditions to block combustion.

Benefits of technology

On the basis of not affecting the electrochemical performance of lithium batteries, the safety of lithium batteries can be improved, and the combustion can be quickly blocked at high temperatures or even after a fire, preventing accidents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701810A_ABST
    Figure CN119701810A_ABST
Patent Text Reader

Abstract

The invention provides a flame-retardant microcapsule, a preparation method thereof and a battery, and belongs to the technical field of batteries. The flame-retardant microcapsule comprises a core body and a shell covering the surface of the core body, the core body comprises a flame retardant, and the shell comprises an inorganic matter modified polymer. And the lithium ion conductivity of the surface of the shell is greater than or equal to 10 <-4 > S / cm. The flame-retardant microcapsule is used for being added into the lithium battery, the shell modified with the inorganic matter with high ionic conductivity can promote the migration rate of lithium ions on the surface of the flame-retardant microcapsule, and the flame-retardant microcapsule can play a flame-retardant role on the basis of not influencing the electrochemical performance of the lithium battery. When the lithium battery is in a normal working state, the flame retardant cannot be released; when the lithium battery is subjected to extreme working conditions such as puncture and thermal runaway, the shell of the flame-retardant microcapsule is melted and broken to release the internal flame retardant, and the flame retardant can play a flame-retardant role, so that combustion is quickly blocked after the lithium battery is at a high temperature or even is on fire, and the safety of the lithium battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a flame retardant microcapsule and a preparation method thereof, and a battery. Background Art

[0002] Most commercial lithium batteries consist of an anode, a cathode, a separator, and an organic liquid electrolyte. The organic liquid electrolyte contains dissolved lithium salts and optimized organic solvents such as propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC). These organic liquid electrolytes have high ionic conductivity (10 at room temperature). -3 S cm -1 ~10 -2 Scm -1 ) and the unique characteristics of good contact with electrodes. However, safety-related issues have limited the development of organic liquid electrolytes, especially in large-scale preparation and application. This means that when lithium batteries are exposed to harsh conditions such as short circuits, high temperatures and battery crushing, toxicity, flammability, potential leakage and even explosion accidents may occur.

[0003] Improvements to improve safety, such as adding flame retardant additives to the electrolyte and replacing the electrolyte with solid electrolytes, often come at the expense of electrochemical performance. For example, flame retardant additives are toxic to the electrolyte, resulting in reduced ion conductivity and deterioration of interfacial film-forming properties. Solid electrolytes have insufficient ion conductivity and large polarization at the electrode interface. Summary of the invention

[0004] The present application provides a flame retardant microcapsule and a preparation method thereof, and a battery. The flame retardant microcapsule can be applied to lithium batteries and improve the safety of lithium batteries without affecting the electrochemical properties of the lithium batteries.

[0005] The embodiment of the present application is implemented as follows:

[0006] In the first aspect, the present application provides a flame retardant microcapsule, which includes a core and a shell coated on the surface of the core, the core includes a flame retardant, and the shell includes an inorganic modified polymer. The lithium ion conductivity of the shell surface is ≥10 - 4 S / cm.

[0007] In the above technical scheme, the present application provides a flame-retardant microcapsule with a core-shell structure, which is used to be added to a lithium battery. The shell modified with an inorganic substance with high ionic conductivity can promote the migration rate of lithium ions on the surface of the flame-retardant microcapsule, that is, the flame-retardant microcapsule can play a flame-retardant function without affecting the electrochemical properties of the lithium battery. When the lithium battery is in a normal working state, the flame-retardant microcapsule maintains a complete shape, that is, the shell can completely cover the internal flame retardant, and the flame retardant will not be released to affect the normal working state of the lithium battery; when the lithium battery is punctured, thermal runaway or other extreme conditions occur, the shell of the flame-retardant microcapsule melts and breaks, thereby releasing the internal flame retardant, and the flame retardant can play a flame-retardant effect, so as to quickly block combustion when the lithium battery is at high temperature or even catches fire, thereby improving the safety of the lithium battery.

[0008] The flame-retardant microcapsules with high surface ionic conductivity provided by the present invention, on the one hand, confine the flame-retardant additives inside the microcapsules without affecting the ionic conductivity and interface characteristics; on the other hand, the lithium ion conductivity on the surface is high, which can effectively reduce the internal resistance and polarization of the battery, and is beneficial to improving the electrochemical performance of the lithium battery.

[0009] In combination with the first aspect, in a first possible example of the first aspect of the present application, the inorganic substance is insoluble in water and does not react with water.

[0010] In the above examples, selecting an inorganic substance that is soluble in water and does not react with water as the material for modifying the polymer is beneficial for preparing an oil phase solution during the preparation of flame retardant microcapsules.

[0011] In combination with the first aspect, in a second possible example of the first aspect of the present application, the intrinsic lithium ion conductivity of the shell surface is ≥10 -4 S / cm, or the lithium ion conductivity of the interface layer formed by the shell and the electrolyte is ≥10 -4 S / cm. The electrolyte includes a liquid electrolyte or a solid electrolyte.

[0012] In the above examples, the lithium ion conductivity of the shell surface is the intrinsic lithium ion conductivity of the shell surface or the lithium ion conductivity of the interface layer formed by the shell and the electrolyte.

[0013] In combination with the first aspect, in a third possible example of the first aspect of the present application, the particle size of the inorganic substance is 100 nm to 1 μm.

[0014] In the above example, by making the particle size of the inorganic substance within the above range, the inorganic substance can better modify the polymer to form the shell of the flame retardant microcapsule, thereby promoting the migration rate of lithium ions on the surface of the flame retardant microcapsule, and then enabling the flame retardant microcapsule to perform the flame retardant function without affecting the electrochemical properties of the lithium battery.

[0015] In combination with the first aspect, in a fourth possible example of the first aspect of the present application, the particle size of the flame retardant microcapsules is 1 μm to 150 μm.

[0016] In the above example, by making the particle size of the flame retardant microcapsules within the above range, the flame retardant microcapsules can be better added to the lithium battery, and the flame retardant microcapsules can play a flame retardant function without affecting the electrochemical performance of the lithium battery.

[0017] In combination with the first aspect, in a fifth possible example of the first aspect of the present application, the polymer is an oil-soluble polymer. Optionally, the polymer includes any one or more of polyethylene, polystyrene, polyoctyl methacrylate and ethylene-acrylate copolymer.

[0018] In the above examples, selecting an oil-soluble polymer as the main material of the flame-retardant microcapsule shell is beneficial to preparing an oil phase solution during the preparation of the flame-retardant microcapsules.

[0019] In the second aspect, the present application provides a method for preparing a flame-retardant microcapsule as described above, which comprises: under stirring, dropping an oil phase solution into a first aqueous phase solution to form an oil-in-water emulsion, reacting for 0.5h to 4h to obtain a mixed solution, adding a second aqueous phase solution to the mixed solution, and standing for 0.5h to 24h to obtain a flame-retardant microcapsule. The oil phase solution comprises a flame retardant, a polymer, an inorganic substance, and a volatile organic solvent. Both the first aqueous phase solution and the second aqueous phase solution comprise water and a surface additive.

[0020] In the above technical scheme, in the preparation method of the flame-retardant microcapsules of the present application, after standing, the volatile organic solvent in the system is completely volatilized, which causes the polymer chains in the polymer to continuously entangle and cross-link, and the inorganic matter to continuously accumulate on the surface of the polymer, and finally form a shell, that is, flame-retardant microcapsules with high ionic conductivity are obtained.

[0021] The method for preparing the flame-retardant microcapsules of the present application can prepare flame-retardant microcapsules with a core-shell structure and a shell surface modified with inorganic substances in only one step. The preparation method is simple and the structure of the prepared flame-retardant microcapsules is stable.

[0022] In combination with the second aspect, in a first possible example of the second aspect of the present application, during the reaction of the oil phase solution and the first aqueous phase solution, the stirring rate is 3000 r / min to 10000 r / min.

[0023] In the above example, by making the stirring speed during the reaction of the oil phase solution and the first aqueous phase solution within the above range, new interfaces can be continuously generated in the mixed solution of the oil phase solution and the first aqueous phase solution, and the strong shearing, dispersion, impact, turbulence and other processes generated by the high-speed rotating rotor cause the material to be cut in the shear gap, quickly broken into particles, shortening the emulsification time and forming a stable water-in-oil emulsion.

[0024] In combination with the second aspect, in a second possible example of the second aspect of the present application, the surface additive includes polyvinyl alcohol.

[0025] In the above examples, polyvinyl alcohol can improve the structural stability of the prepared flame retardant microcapsules and improve the morphological integrity of the prepared flame retardant microcapsules.

[0026] In a third aspect, the present application example provides a battery comprising the flame retardant microcapsule as described above. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 Schematic diagram of the structure of the flame retardant microcapsule of the embodiment of the present application.

[0029] Figure 2 This is a projection electron microscope image of the flame retardant microcapsules prepared in Example 1 of the present application.

[0030] Figure 3 This is a comparison chart of the first cycle charge and discharge performance curves of a button battery made of a lithium titanium aluminum phosphate shell-coated microcapsule silicon negative electrode of Example 1 of the present application and a button battery made of a pure silicon negative electrode without microcapsules.

[0031] Figure 4 The figure is a comparison chart of the cycle performance of a button cell made of a silicon negative electrode with a microcapsule coated with a titanium dioxide shell according to Example 2 of the present application and a button cell made of a pure silicon negative electrode without microcapsules.

[0032] Icon: 10-flame retardant microcapsule; 100-core; 200-shell. DETAILED DESCRIPTION

[0033] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0034] Currently, lightweight, rechargeable and powerful lithium batteries (LiBs, also defined as lithium secondary batteries) can store large amounts of energy from solar and wind power, creating a "rechargeable world" and making a fossil fuel-free society possible. They are currently considered to have forward-looking functions in the global efforts to meet the challenges of renewable and mobile energy supply. Lithium batteries have become dominant in electronic devices ranging from handheld to large-scale electronic devices due to their advantages such as safety, high output voltage, high capacity, high energy density, long cycle life, negligible memory effect and low self-discharge. With the profound changes in science and technology, people are in urgent need of "good enough" lithium batteries with higher electrochemical performance, safety, flexibility and biodegradability.

[0035] However, when lithium batteries are exposed to harsh conditions such as short circuits, high temperatures, and battery crushing, toxicity, flammability, potential leakage, and even explosion accidents may occur. In addition, the high reactivity between lithium electrodes and liquid electrolytes can lead to the formation of an uneven solid electrolyte interface (SEI) film. In addition, when overcharged, lithium dendrites will inevitably grow from the damaged SEI film, which will lead to poor performance, lithium dead spots, and safety issues. Therefore, the safety of lithium batteries has received widespread attention.

[0036] In order to improve the safety of lithium batteries, flame retardants can be added to lithium batteries to quickly block combustion at high temperatures or even after fire, thereby improving the safety of lithium batteries. However, adding flame retardants directly to positive electrode materials, negative electrode materials or electrolytes will inhibit ion transmission, reduce material transmission rates, etc., thus seriously affecting the electrical performance of lithium batteries.

[0037] In order to overcome the above shortcomings, the flame retardant can be encapsulated in a shell material to form a flame retardant microcapsule. The shell of the flame retardant microcapsule can melt when the battery has thermal runaway, releasing the flame retardant inside.

[0038] The following is a detailed description of a flame retardant microcapsule and a preparation method thereof and a battery according to an embodiment of the present application:

[0039] See also Figure 1 The present application provides a flame retardant microcapsule 10 , which includes a core 100 and a shell 200 , wherein the shell 200 is coated on the surface of the shell 200 .

[0040] In order to prevent the core 100 from being released from the shell 200 , the shell 200 completely covers the outer surface of the core 100 , or the shell 200 has holes with a hole diameter smaller than the particle diameter of the core 100 .

[0041] The core 100 includes a flame retardant.

[0042] It should be noted that the embodiment of the present application does not limit the type of flame retardant in the flame retardant microcapsule 10, but generally an additive flame retardant is selected. The additive flame retardant can be added to the material that needs to be flame retardant by a mechanical mixing method to make it flame retardant. The additive flame retardant mainly includes organic flame retardants and inorganic flame retardants. The organic flame retardant is some flame retardants represented by bromine, phosphorus-nitrogen, nitrogen, red phosphorus and compounds. The inorganic flame retardant is mainly antimony trioxide, magnesium hydroxide, aluminum hydroxide, silicon and other flame retardant systems.

[0043] As an example, the embodiments of the present application may select phosphorus-nitrogen flame retardants, including phosphate esters, carbamates, tripolyphosphates, and the like.

[0044] The housing 200 includes an inorganic modified polymer.

[0045] The lithium ion conductivity on the surface of the shell 200 is ≥10 -4 S / cm.

[0046] The intrinsic lithium ion conductivity of the shell 200 surface is ≥10 -4 S / cm, or the lithium ion conductivity of the interface layer formed by the shell 200 and the electrolyte is ≥10 -4 S / cm. The electrolyte includes a liquid electrolyte or a solid electrolyte.

[0047] Optionally, the lithium ion conductivity on the surface of the housing 200 is ≥5*10 -4 S / cm.

[0048] Optionally, the inorganic material is insoluble in water and does not react with water.

[0049] Selecting inorganic substances that are soluble in water and do not react with water as the material for modifying the polymer is beneficial for preparing an oil phase solution during the process of preparing the flame retardant microcapsules 10 .

[0050] Optionally, the inorganic substance includes ceramic particles, and the ceramic particles include at least one of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, titanium dioxide and silicon dioxide.

[0051] Optionally, the ceramic particles include lithium aluminum titanium phosphate and / or titanium dioxide.

[0052] The ionic conductivity of the above ceramic particles is greater than or equal to 10 -4S / cm, and the above-mentioned ceramic particles are insoluble in water and do not react with water. Both materials can be used to modify the polymer to form the shell 200 of the flame retardant microcapsule 10, thereby promoting the migration rate of lithium ions on the surface of the flame retardant microcapsule 10, so that the flame retardant microcapsule 10 can play a flame retardant function without affecting the electrochemical properties of the lithium battery.

[0053] It should be noted that, in the embodiments of the present application, lithium aluminum titanium phosphate and lithium aluminum germanium phosphate may be mixed for use, or lithium aluminum titanium phosphate may be used alone, or lithium aluminum germanium phosphate may be used alone.

[0054] Optionally, the particle size of the inorganic substance is 100 nm to 1 μm.

[0055] By making the particle size of the inorganic substance within the above range, the inorganic substance can better modify the polymer to form the shell 200 of the flame-retardant microcapsule 10, thereby promoting the migration rate of lithium ions on the surface of the flame-retardant microcapsule 10, and thus enabling the flame-retardant microcapsule 10 to perform the flame-retardant function without affecting the electrochemical properties of the lithium battery.

[0056] As an example, the particle size of the inorganic substance may be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, or 1 μm.

[0057] Optionally, the polymer is an oil-soluble polymer, and the molecular weight of the oil-soluble polymer is 3,000-100,000.

[0058] Oil-soluble polymers are polymers that are molecularly dispersible in non-polar solvents (such as benzene, xylene, gasoline, kerosene, diesel, etc.). Selecting oil-soluble polymers as the main material of the shell 200 of the flame-retardant microcapsule 10 is conducive to obtaining an oil phase solution during the preparation of the flame-retardant microcapsule 10.

[0059] Optionally, the polymer includes any one or more of polyethylene, polystyrene, polyoctyl methacrylate and ethylene-acrylate copolymer.

[0060] Optionally, the particle size of the flame retardant microcapsule 10 is 1 μm to 150 μm.

[0061] By making the particle size of the flame retardant microcapsule 10 within the above range, the flame retardant microcapsule 10 can be better added to the lithium battery, and the flame retardant microcapsule 10 can exert the flame retardant function without affecting the electrochemical performance of the lithium battery.

[0062] As an example, the particle size of the flame retardant microcapsule 10 may be 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 50 μm, 80 μm, 100 μm, 120 μm or 150 μm.

[0063] The present application provides a flame-retardant microcapsule 10 with a core-shell structure. The flame-retardant microcapsule 10 is used to be added to a lithium battery. The shell 200 modified with an inorganic substance having high ionic conductivity can promote the migration rate of lithium ions on the surface of the flame-retardant microcapsule 10, that is, the flame-retardant microcapsule 10 can play a flame-retardant function without affecting the electrochemical properties of the lithium battery. When the lithium battery is in a normal working state, the flame-retardant microcapsule 10 maintains a complete shape, that is, the shell 200 can completely cover the internal flame retardant, and the flame retardant will not be released to affect the normal working state of the lithium battery; when the lithium battery is punctured, thermal runaway or other extreme conditions occur, the shell 200 of the flame-retardant microcapsule 10 melts and breaks, thereby releasing the internal flame retardant, and the flame retardant can play a flame-retardant effect, and quickly block combustion after the lithium battery is at high temperature or even catches fire, thereby improving the safety of the lithium battery.

[0064] The present application also provides a method for preparing flame-retardant microcapsules, which comprises:

[0065] S1. Preparation of oil phase solution and water phase solution

[0066] The flame retardant, polymer and inorganic substance are dissolved in a volatile organic solvent according to a proportion to prepare an oil phase solution.

[0067] Among them, the mass ratio of flame retardant, polymer, inorganic matter and volatile organic solvent is 3.6-5.3:2.2-2.8:0.01-0.5:50-100.

[0068] Volatile organic solvents are a class of organic liquids that can evaporate at normal low temperatures.

[0069] Optionally, the volatile organic solvent includes any one or more of dichloromethane, acetone and chloroform.

[0070] The surface additive is dissolved in water to prepare an aqueous phase solution.

[0071] The mass percentage of the surface additive in the aqueous solution is 1wt% to 10wt%.

[0072] Among them, the surface additive includes polyvinyl alcohol.

[0073] Polyvinyl alcohol can improve the structural stability of the prepared flame retardant microcapsules and improve the morphological integrity of the prepared flame retardant microcapsules.

[0074] The water can be deionized water or ultrapure water.

[0075] S2. Preparation of flame retardant microcapsules

[0076] At a temperature of 5°C to 30°C, pour the first aqueous phase solution into a shear mixer, turn on the shear mixer and start stirring, add the oil phase solution dropwise into the first aqueous phase solution to form an oil-in-water emulsion, react for 0.5h to 4h to obtain a mixed solution, add the second aqueous phase solution to the mixed solution to dilute the emulsion, let it stand for 0.5h to 24h until the volatile organic solvent is completely evaporated, and obtain flame retardant microcapsules.

[0077] The first aqueous phase solution and the second aqueous phase solution are both prepared aqueous phase solutions, and the volume ratio of the oil phase solution, the first aqueous phase solution and the second aqueous phase solution is 0.8-1.2:0.8-1.2:1.5-3.

[0078] Wherein, the stirring rate of the shear mixer is 3000r / min to 10000r / min.

[0079] By making the stirring speed during the reaction of the oil phase solution and the first aqueous phase solution within the above range, new interfaces can be continuously generated in the mixed solution of the oil phase solution and the first aqueous phase solution. The strong shearing, dispersion, impact, turbulence and other processes generated by the high-speed rotating rotor cause the material to be cut in the shear gap and quickly broken into particles, thereby shortening the emulsification time and forming a stable water-in-oil emulsion.

[0080] Optionally, the dropping rate of the oil phase solution is 30 mL / min to 70 mL / min.

[0081] In the preparation method of the flame-retardant microcapsules of the present application, after standing, the volatile organic solvent in the system is completely volatilized, which causes the polymer chains in the polymer to continuously entangle and cross-link, and the inorganic matter to continuously accumulate on the surface of the polymer, and finally form a shell, thereby obtaining flame-retardant microcapsules with high ionic conductivity.

[0082] The method for preparing the flame-retardant microcapsules of the present application can prepare flame-retardant microcapsules with a core-shell structure and a shell surface modified with inorganic substances in only one step. The preparation method is simple and the structure of the prepared flame-retardant microcapsules is stable.

[0083] The present application also provides a battery, which includes the flame retardant microcapsule as described above.

[0084] In the battery of the present application, the flame retardant microcapsules may be coated on the surface of the diaphragm, or coated on the surface of the positive electrode plate, or coated on the surface of the negative electrode plate, or added to the electrolyte.

[0085] The flame retardant microcapsules and the preparation method thereof of the present application are further described in detail below in conjunction with the examples.

[0086] Example 1

[0087] The present invention provides a flame retardant microcapsule and a preparation method thereof, which comprises the following steps:

[0088] S1. Preparation of oil phase solution and water phase solution

[0089] Trichloroethyl phosphate, polystyrene and lithium aluminum titanium phosphate are dissolved in dichloromethane and mixed evenly under stirring conditions to prepare an oil phase solution.

[0090] Among them, the mass ratio of trichloroethyl phosphate, polystyrene, lithium aluminum titanium phosphate and dichloromethane is 3.8:2.5:0.05:70.

[0091] The particle size of inorganic substances is 100nm to 1μm.

[0092] The molecular weight of polystyrene is 25,000.

[0093] Polyvinyl alcohol was dissolved in deionized water to prepare an aqueous solution, wherein the concentration of the polyvinyl alcohol aqueous solution was 2 wt %.

[0094] S2. Preparation of flame retardant microcapsules

[0095] At a temperature of 25°C, the first aqueous phase solution was poured into a shear mixer, the shear mixer was turned on and stirring began, the oil phase solution was added dropwise to the first aqueous phase solution at a rate of 60 mL / min to form an oil-in-water emulsion, and after reacting for 1 hour, a mixed solution was obtained, and the second aqueous phase solution was added to the mixed solution to dilute the emulsion. After standing for 24 hours, the volatile organic solvent was completely evaporated to obtain flame retardant microcapsules.

[0096] The first aqueous phase solution and the second aqueous phase solution are both prepared aqueous phase solutions, and the volume ratio of the oil phase solution, the first aqueous phase solution and the second aqueous phase solution is 1:1:2.

[0097] The stirring rate of the shear mixer is 6000 r / min.

[0098] The average particle size of the flame retardant microcapsules is 5 μm.

[0099] Figure 2 This is a transmission electron microscope image of the flame retardant microcapsules prepared in Example 1.

[0100] Example 2

[0101] The embodiments of the present application provide a flame retardant microcapsule and a preparation method thereof. Embodiment 2 is based on Embodiment 1, except that the inorganic substance is changed to titanium dioxide, and the other substances remain unchanged.

[0102] The particle size of the prepared flame retardant microcapsules is 8 μm.

[0103] The flame retardant microcapsules of Example 2 of the present application can be used to make solid-state batteries, and the method is as follows:

[0104] S1. Preparation of electrode slurry:

[0105] Weigh 0.05g of CMC powder and dissolve it in water to form a solution with a concentration of 1%, and use it together with 0.05g of SBR as a binder for the negative electrode slurry; weigh 0.35g of nano silicon powder and 0.05g of conductive agent Super P, add them to a weighing bottle, and add the CMC solution thereto; perform three consecutive ball milling stirrings, each for 15 minutes, then add 0.05g of SBR, perform the last ball milling stirring to form a silicon negative electrode slurry that can be coated; add 0.05g of the flame retardant microcapsule powder prepared in Example 2 (this step is not required for button cells that do not contain flame retardant microcapsules), and use magnetic stirring to stir the above slurry for 1 hour at a rate of 650rpm.

[0106] S2. Solid-state battery preparation:

[0107] In the glove box, CR2032 button cells were assembled in the order of electrode plate / PEO+LiTFSI solid electrolyte membrane / lithium plate / gasket / spring plate. After standing at room temperature for 12 hours, subsequent electrochemical performance tests were performed.

[0108] Among them, the PEO+LiTFSI solid electrolyte membrane is prepared by casting method, and the process is as follows: 0.6g PEO, 0.326g LiTFSI (EO: Li + =12:1), 15 mL of acetonitrile was mixed and stirred for 5 h to obtain a PEO / LiTFSI solution; the obtained solution was poured into a polytetrafluoroethylene dish, dried at room temperature for 24 h, vacuum dried at 55 °C for 24 h, transferred to a glove box, and continued to dry for 24 h to obtain a PEO+LiTFSI solid electrolyte membrane.

[0109] Example 3

[0110] The embodiments of the present application provide a flame retardant microcapsule and a preparation method thereof. Embodiment 3 is based on Embodiment 1, in which only the inorganic substance is changed to silicon dioxide, and the other substances remain unchanged.

[0111] The particle size of the prepared flame retardant microcapsules is 6 μm.

[0112] The flame retardant microcapsules of Example 3 of the present application can be used to make solid-state batteries, and the method is as follows:

[0113] S1. Preparation of electrode slurry:

[0114] Weigh 0.05g of CMC powder and dissolve it in water to form a solution with a concentration of 1%, and use it together with 0.05g of SBR as a binder for the negative electrode slurry; weigh 0.35g of nano silicon powder and 0.05g of conductive agent Super P, add them to a weighing bottle, and add the CMC solution thereto; perform three consecutive ball milling stirrings, each for 15 minutes, then add 0.05g of SBR, perform the last ball milling stirring to form a silicon negative electrode slurry that can be coated; add 0.05g of the flame retardant microcapsule powder prepared in Example 3 (this step is not required for button cells that do not contain flame retardant microcapsules), and use magnetic stirring to stir the above slurry for 1 hour at a rate of 650rpm.

[0115] S2. Solid-state battery preparation:

[0116] In the glove box, the obtained DOL in-situ polymerized electrolyte precursor solution was dripped onto the surface of the positive electrode, negative electrode and diaphragm in the order of electrode plate / DOL in-situ polymerized electrolyte / lithium plate / gasket / spring plate to assemble the CR2032 button cell. After standing at room temperature for 48 hours, the subsequent electrochemical performance tests were carried out.

[0117] The DOL in-situ polymerized electrolyte precursor is a mixed solution containing 0.5 mL DOL, 0.5 mL DME, and 0.303 g LiPF6, which is obtained by stirring for 1 hour.

[0118] Test Example 1

[0119] The flame-retardant microcapsules prepared in Example 1 were taken, and the negative electrode plates were respectively assembled into button batteries. The first cycle charge and discharge performance curves of the button batteries made of the flame-retardant microcapsules coated with lithium titanium aluminum phosphate shells of Example 1 of the present application and the button batteries made of pure silicon negative electrodes without flame-retardant microcapsules were measured respectively. Figure 3 shown.

[0120] The method of making flame retardant microcapsules into button batteries is as follows:

[0121] Electrode slurry preparation:

[0122] Weigh 0.05g of CMC powder and dissolve it in water to form a solution with a concentration of 1%, and use it together with 0.05g of SBR as a binder for the negative electrode slurry; weigh 0.35g of nano silicon powder and 0.05g of conductive agent Super P, add them to a weighing bottle, and add the CMC solution thereto; perform three consecutive ball milling stirrings, each for 15 minutes, then add 0.05g of SBR, perform the last ball milling stirring to form a silicon negative electrode slurry that can be coated; add 0.05g of the flame retardant microcapsule powder prepared in Example 1 (this step is not required for button cells that do not contain flame retardant microcapsules), and use magnetic stirring to stir the above slurry for 1 hour at a rate of 650rpm.

[0123] Electrode sheet preparation:

[0124] The slurry was evenly coated on a smooth and clean copper foil with a scraper, and the wet film thickness was 250 μm. After the coating was completed, the silicon negative electrode was placed in a vacuum oven at 80°C for 12 hours. The silicon negative electrode was cut into circular electrodes with a diameter of 12 mm for standby use, and weighed after drying.

[0125] Button cell preparation:

[0126] In the glove box, CR2032 button cells were assembled in the order of electrode plate / diaphragm / lithium plate / gasket / spring plate. The electrolyte was LB-011 and the diaphragm was Celgard 2500. After standing at room temperature for 12 hours, the subsequent electrochemical performance tests were carried out.

[0127] like Figure 3 As shown, Figure 3 The first cycle charge and discharge performance curve comparison diagram of a button cell made of a silicon negative electrode coated with a lithium titanium aluminum phosphate shell microcapsule of Example 1 of the present application and a button cell made of a pure silicon negative electrode without microcapsules. At a current density of 0.42A / g, the electrode discharge specific capacity of the button cell containing the flame-retardant microcapsules of Example 1 of the present application reaches 1926.5mAh / g, and the electrode discharge specific capacity of the button cell without the flame-retardant microcapsules is 1875.4mAh / g. The electrode discharge specific capacity of the button cell containing the flame-retardant microcapsules of Example 1 of the present application is significantly better than that of the button cell without the flame-retardant microcapsules.

[0128] Test Example 2

[0129] The flame retardant microcapsules prepared in Examples 1 and 2 were respectively prepared into button batteries, and the cycle performance of the button batteries containing the flame retardant microcapsules of Examples 1 and 2 and the button batteries without the flame retardant microcapsules were measured respectively. The results are shown in Tables 1 and Figure 4 shown.

[0130] The method of making flame retardant microcapsules into button batteries is as follows:

[0131] Electrode slurry preparation:

[0132] Weigh 0.05g of CMC powder and dissolve it in water to form a solution with a concentration of 1%, and use it together with 0.05g of SBR as a binder for the negative electrode slurry; weigh 0.35g of nano silicon powder and 0.05g of conductive agent Super P, add them to a weighing bottle, and add the CMC solution thereto; perform three consecutive ball milling stirrings, each for 15 minutes, then add 0.05g of SBR, perform the last ball milling stirring to form a silicon negative electrode slurry that can be coated; add 0.05g of the flame retardant microcapsule powder prepared in Examples 1 to 2 (this step is not required for button cells that do not contain flame retardant microcapsules), and use magnetic stirring to stir the above slurry for 1 hour at a rate of 650rpm.

[0133] Electrode sheet preparation:

[0134] The slurry was evenly coated on a smooth and clean copper foil with a scraper, and the wet film thickness was 250 μm. After the coating was completed, the silicon negative electrode was placed in a vacuum oven at 80°C for 12 hours. The silicon negative electrode was cut into circular electrodes with a diameter of 12 mm for standby use, and weighed after drying.

[0135] Button cell preparation:

[0136] In the glove box, CR2032 button cells were assembled in the order of electrode plate / diaphragm / lithium plate / gasket / spring plate. The electrolyte was LB-011 and the diaphragm was Celgard 2500. After standing at room temperature for 12 hours, the subsequent electrochemical performance tests were carried out.

[0137] The cycle performance test method of button batteries is as follows:

[0138] In the battery test cabinet, cycle 1 cycle at 0.01-1.2V, 0.42A / g current density, then cycle 50 cycles at 0.05-1.2V, 0.84A / g current density, and test and record its discharge specific capacity.

[0139] Table 1 Cycling performance of button cells containing the flame retardant microcapsules of Examples 1 to 2 and button cells without flame retardant microcapsules

[0140] project Discharge specific capacity (mAh / g) Example 1 1926.5 Example 2 1790.4 Does not contain flame retardant microcapsules 1655.7

[0141] From Table 1 and Figure 4 It can be seen that Figure 4 The figure is a comparison of the cycle performance of a button cell made of a silicon anode containing a microcapsule coated with a titanium dioxide shell according to Example 2 of the present application and a button cell made of a pure silicon anode without microcapsules. The discharge specific capacity of the button cell made of the flame-retardant microcapsules of Examples 1 and 2 after 50 cycles is higher than the discharge specific capacity of the button cell without the flame-retardant microcapsules after 50 cycles.

[0142] The above description is only a specific embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A flame retardant microcapsule, characterized in that: The flame retardant microcapsule comprises a core and a shell coated on the surface of the core, the core comprises a flame retardant, and the shell comprises an inorganic modified polymer; The lithium ion conductivity of the shell surface is ≥10 -4 S / cm.

2. The flame retardant microcapsule according to claim 1, characterized in that: The inorganic substance is insoluble in water and does not react with water.

3. The flame retardant microcapsule according to claim 1, characterized in that: The intrinsic lithium ion conductivity of the shell surface is ≥10 -4 S / cm, or the lithium ion conductivity of the interface layer formed by the shell and the electrolyte is ≥10 -4 S / cm; Wherein, the electrolyte includes a liquid electrolyte or a solid electrolyte.

4. The flame retardant microcapsule according to claim 1, characterized in that: The particle size of the inorganic substance is 100nm to 1μm.

5. The flame retardant microcapsule according to claim 1, characterized in that: The particle size of the flame retardant microcapsule is 1 μm to 150 μm.

6. The flame retardant microcapsule according to claim 1, characterized in that: The polymer is an oil-soluble polymer; Optionally, the polymer includes any one or more of polyethylene, polystyrene, polyoctyl methacrylate and ethylene-acrylate copolymer.

7. A method for preparing the flame retardant microcapsules according to any one of claims 1 to 6, characterized in that: The preparation method of the flame retardant microcapsules comprises: under stirring, dropping an oil phase solution into a first water phase solution to form an oil-in-water emulsion, reacting for 0.5h to 4h to obtain a mixed solution, adding a second water phase solution to the mixed solution, and standing for 0.5h to 24h to obtain flame retardant microcapsules; Wherein, the oil phase solution comprises the flame retardant, the polymer, the inorganic substance and a volatile organic solvent; The first aqueous phase solution and the second aqueous phase solution both include water and a surface additive.

8. The method for preparing flame retardant microcapsules according to claim 7, characterized in that: During the reaction of the oil phase solution and the first water phase solution, the stirring rate is 3000 r / min to 10000 r / min.

9. The method for preparing flame-retardant microcapsules according to claim 7, characterized in that: The surface additive includes polyvinyl alcohol.

10. A battery, characterized in that: The battery comprises the flame retardant microcapsule according to any one of claims 1 to 6.

Citation Information

Cited By

  • Composite solid electrolyte diaphragm and preparation method thereof

    CN121238157A